Stress, Anxiety And Depression Status Of Malaysian Public In Relation To The Covid-19 Pandemic And Movement Control Order - Sharifah Najwa Syed Mohamad; Sharifah Fairuz Syed Mohamad; Fathima Begum Syed Mohideen; Fatin Ahza Rosli; Nur Faraheen Abdul Rahman; Shahrina Ismail (Zes Rokman Resources, 2024)
Vol. 16 (June) page: 1-7